2017
DOI: 10.1016/j.joca.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of medial femoral knee cartilage volume – analysis of the OA Biomarkers Consortium FNIH Study cohort

Abstract: OBJECTIVE Large studies of knee osteoarthritis (KOA) require well-characterized efficient methods to assess progression. We previously developed the local-area cartilage segmentation (LACS) software method, to measure cartilage volume on MRI scans. The present study further validates this method in a larger patient cohort and assesses predictive validity in a case-control study. METHOD The OA Biomarkers Consortium FNIH Project, a case-control study of KOA progression nested within the Osteoarthritis Initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…These data agree with results from the Foundation for National Institute of Health (FNIH) initiative on PIIANP [22], another type II collagen biomarker indicative of collagen formation. In addition, cartilage oligomeric protein (COMP) and urinary CTX-II (uCTX-II) have all shown potential as prognostic biomarkers [22][23][24][25][26][27]. Interestingly, however, uCTX-II and PIIANP did not provide the same prognostic, nor predictive value in the current study (see supplementary data Fig.…”
Section: Discussionmentioning
confidence: 51%
“…These data agree with results from the Foundation for National Institute of Health (FNIH) initiative on PIIANP [22], another type II collagen biomarker indicative of collagen formation. In addition, cartilage oligomeric protein (COMP) and urinary CTX-II (uCTX-II) have all shown potential as prognostic biomarkers [22][23][24][25][26][27]. Interestingly, however, uCTX-II and PIIANP did not provide the same prognostic, nor predictive value in the current study (see supplementary data Fig.…”
Section: Discussionmentioning
confidence: 51%
“…First, while we showed correlations between 2‐D and 3‐D UTE‐T2*, our ability to characterize possible UTE‐T2* changes 2 years after ACLR was limited by relatively small numbers. Second, the 3‐D femoral “tread mark” ROIs studied in this work are modeled after those found to be the most responsive to cartilage volume change and radiographic progression in an OA population. While our tread mark ROIs encompass the majority of the central weight‐bearing medial tibiofemoral surfaces in the knee previously shown to be most responsive to volume change and radiographic progression, peripheral medial cartilage regions and cartilage to the lateral, patellar, and trochlear compartments was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts were recently undertaken under the auspices of the Foundation for the National Institutes of Health (FNIH) OA Biomarkers Consortium 813 , and we previously reported that one- and two-year (BL→Y1 and BL→Y2) loss in central medial femorotibial cartilage thickness was associated with the combination of pain and radiographic progression in knee OA from baseline (BL) to up to year four follow-up (BL→Y4) 8 and this association was found to be stronger for radiographic progression than for pain progression More recently, Schaefer et al used the FNIH design to validate a new cartilage segmentation method 12 and reported odds ratios for change in cartilage volume in localized areas of the medial femur that were in the same range as that observed in the FNIH study for cartilage thickness 8 .…”
Section: Introductionmentioning
confidence: 98%